Achieving Goals in Effectiveness of the Two-Wheel Vehicle Tax Clearance Program at the Joint Office of SAMSAT Krian, Sidoarjo Regency - Nurainiyah Nurainiyah; Ilmi Usrotin Choiriyah (Universitas Muhammadiyah Sidoarjo, 2022)
The results of the study were not achieved in achieving the goals of the bleaching program. Clarity of strategy in achieving goals has been carried out by the office with the SAMSAT but not optimally so that the goal has not been achieved, the availability of work facilities and infrastructure in the SAMSAT office is well-available and effective and efficient implementation of the whitening program has been implemented. Program, Bleaching, Motor Vehicle Tax The whitening program is the abolition of motor vehicle tax administration sanctions in the form of motor vehicle tax fines issued by the governor, which aims to increase public compliance and awareness in paying motor vehicle taxes. The whitening program has been implemented at the Joint Office of the Krian Samsat, Sidoarjo Regency, but there are still taxpayers who are in arrears in paying the two-wheeled motorized vehicle tax so that the whitening program has not yet reached the specified target. The research method uses descriptive qualitative. Data were obtained through interviews, observation and documentation. The results of the study were not achieved in achieving the goals of the bleaching program. clarity of goals to be achieved is clear. Clarity of strategy in achieving goals has been carried out by the office with the SAMSAT but not optimally so that the goal has not been achieved, the availability of work facilities and infrastructure in the SAMSAT office is well available and, effective and efficient implementation of the whitening program has been implemented.